Do prenatal exposures pose a real threat to ovarian function? Bisphenol A as a case study. Issue 4 (April 2019) - Mathew, Hannah; Mahalingaiah, Shruthi
Abstract : Fetal development represents a time of potential vulnerability due to rapid cell division, organ development and limited fetal kidney/liver activity for detoxification and metabolism of exposures. Health effects of prenatal toxicant exposure have previously been described, but there is little cohesive evidence surrounding effects on ovarian function. Using bisphenol A (BPA) as a case study, we seek to examine whether a prominent prenatal environmental exposure can pose a real threat to human ovarian function. To do so, we broadly review human oogenesis and menstrual cycle biology. We then present available literature addressing prenatal bisphenol A and diverse outcomes at the level of the ovary. We highlight relevant human cohorts and mammalian models to review the existing data on prenatal exposures and ovarian disruption. Doing so suggests that while current exposures to BPA have not shown marked or consistent results, there is data sufficient to raise concerns regarding ovarian function. Challenges in the examination of this question suggest the need for additional models and pathways by which to expand these examinations in humans.